Correlation between arch form and facial form: A cross sectional study - Sanjna Nayar; Aruna; Santhosh; Wasim Manzoor (Wolters Kluwer Medknow Publications, 2015)
Arch form is a key determinant in teeth position. Teeth selection and placement must be based on the functional and esthetic needs of the patient. Keeping in mind, the biomechanics involved with the prosthesis. The aim of the study was to evaluate the correlation between arch form and facial form. About 40 individuals in the age group of 20-25 years were involved in the study. The arch form and facial form were analyzed statistically to check for any correlation. It was found that, 63.63% of leptoprosophic individuals had squarish arch form while, 54.6% of mesoprosophic faces had ovoid arch form.